Science policy frameworks for a post-pandemic green economic recovery. (January 2023) - Zachariadis, Theodoros; Giannakis, Elias; Taliotis, Constantinos; Karmellos, Marios; Fylaktos, Nestor; Howells, Mark; Blyth, Will; Hallegatte, Stéphane
Abstract: As current production and consumption patterns exceed planetary boundaries, many leaders have stressed the need to adopt green economic stimulus policies in the aftermath of the COVID-19 pandemic. This paper provides an integrated multi-stakeholder framework to design an economic recovery strategy aligned with climate stabilisation objectives. We first employ quantitative energy and economic models, and then a multi-criteria decision process in which we engage social actors from government, enterprises and civil society. As a case study, we select green recovery measures that are relevant for a European Union country and assess their appropriateness with numerous criteria related to climate resilience and socio-economic sustainability. Results highlight trade-offs between immediate and long-run effects, economic and environmental objectives, and expert evidence and societal priorities. Importantly, we find that a 'return-to-normal' economic stimulus is environmentally unsustainable and economically inferior to most green recovery schemes. Highlights: COVID-19 post-pandemic stimulus packages can assist with global climate goals. Selection of recovery measures can incorporate a multi-stakeholder process. Energy and economic models are combined with multi-criteria assessment methods. Green recovery measures can be very effective in stimulating growth. Attractiveness of measures varies between the short-term and long-term.